2018
DOI: 10.1371/journal.pone.0198209
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of surgical sterilization on owned dog population size in Villa de Tezontepec, Hidalgo, Mexico, using an individual-based computer simulation model

Abstract: Surgical sterilization programs for dogs have been proposed as interventions to control dog population size. Models can be used to help identify the long-term impact of reproduction control interventions for dogs. The objective of this study was to determine the projected impact of surgical sterilization interventions on the owned dog population size in Villa de Tezontepec, Hidalgo, Mexico. A stochastic, individual-based simulation model was constructed and parameterized using a combination of empirical data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Our results suggest that targeting efforts to reduce abandonment could be as important as directing efforts to reduce the birth rate or increase the removal rate. These findings are in line with those in previous modelling studies reporting synergistic effects of combined fertility control and restricted movement of owned dogs [26] , and emphasising the potential impact of owned dog abandonment dampening the effectiveness of CNR interventions [15,17,22] . Future dog population management efforts should aim to identify the sources of population increase (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that targeting efforts to reduce abandonment could be as important as directing efforts to reduce the birth rate or increase the removal rate. These findings are in line with those in previous modelling studies reporting synergistic effects of combined fertility control and restricted movement of owned dogs [26] , and emphasising the potential impact of owned dog abandonment dampening the effectiveness of CNR interventions [15,17,22] . Future dog population management efforts should aim to identify the sources of population increase (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…System dynamics modelling allows complex and interactive systems to be explained and the impact of interventions on model behaviour to be evaluated [13,14] . Dog population dynamics have been investigated with both system dynamics approaches [15][16][17][18][19][20][21][22][23] and agent-based models [24,25] , assessing the effects of management strategies on population size [15,21,22,25,26] , euthanasia rates [23] , and disease dynamics [19,20] . Most previous studies have modelled dynamics within a single subset of the population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, the model developed by Kisiel et al offered that, regardless of dog age and sex, following 8.6–34.5% annual sterilization, the dog population size after 20 years was reduced between 14 and 79% compared to the absence of intervention. They concluded that sterilization of only young, female dogs has the greatest impact on population reduction of 90–91% 32 . Another study on owned dog population in Italy estimated that to stop population growth, a sterilization rate of > 55% is needed and concluded that only 26% sterilization of female young dogs is adequate to halt dog population growth.…”
Section: Discussionmentioning
confidence: 99%
“…Female dogs in reproductive age are central to any FRD population control program. Findings of a study performed in Mexico suggested that sterilization of young female dogs can enhance reductions in owned dog population size in a 20-year horizon, compared to the current sterilization strategy focused on dogs, regardless of age and sex 32 . Nonetheless little is known on the impact of sterilizing unowned female dogs population.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing the number of free-roaming dogs, particularly in the endemic areas, should be strongly implemented, focusing on young, female dogs. A previous individual-based model strongly suggested that neutralizing only young, female dogs was the best population control strategy (reducing 90–91%) compared to targeting female dogs of any age or mixed-sex sterilization of only young dogs (reducing 82–92%) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%